Hubungan Antara Readiness for Change dan Kinerja Karyawan Industri Selama Pandemi Covid-19 - Yohana Listiyono Putri; Doddy Hendro Wibowo (Bulletin of Counseling and Psychotherapy, 2022)
Employees are required to have readiness for change in facing changes that occur in the era of the Covid-19 pandemic so that performance is maintained correctly. This study aims to determine the relationship between readiness for change and the performance of industrial employees during the Covid-19 pandemic. The participants in this study were 100 industrial employees with a sampling technique, namely simple random sampling, spread across Semarang Regency and Semarang City, with an age range of 23-50 years. Data collection uses the Employee Performance Scale (EPS) by Halim (2016) and the readiness for change scale by Mubarak (2017). The results showed a positive relationship between the variables readiness for change and employee performance with a correlation coefficient of r = 458 and a significance of 0.000 (p<0.05). This means that the higher the readiness for change, the higher the performance of industrial employees during the Covid-19 pandemic. The results in this study, through readiness for change, can be used to maintain and improve the performance of industrial employees during the Covid-19 pandemic.